Implementation of Problem Based Learning Model to Improve Fraction Story Problem Solving Skills - Melda Indah Cahyani; Siti Tika Hadiat; Aan Nurhasanah (COMPETITIVE: Journal of Education, 2024)
This article is written to see the implementation of the problem based learning model to improve fraction story problem solving skills. The research method used in writing this article is a qualitative method with a descriptive approach. Data collection techniques are carried out through: first, in-depth interviews; second, participant observation and third, documentation. While the data collected through the three techniques above are then checked for validity by checking credibility. The results of the study on the application of the problem based learning model to improve fraction story problem solving skills can improve the abilities of fourth grade students of SDN 1 Babakanmulya. This increase can be proven by the increase in the value of the ability to solve fraction story problems in the post-test results after the application of the Problem Based Learning model. In the initial condition, the average value of solving fraction story problems was <60, while after the application of the PBL model, the results obtained by students were above >60. This shows that the PBL model is relevant to be applied to mathematics learning.